(untitled) (South East Asia Journal of Public Health, 2017)
Patients’ knowledge and attitudes have an impact on the management of their illnesses. Obtaining information about the level of awareness is the first step in formulating a preventive program for any health problem. The aim of this study is to assess the knowledge, attitude and practice of hypertensive patients about their disease. A consecutive non- probability sampling technique was adopted to collect all adult hypertensive patients that attended the outpatient clinic of the main three teaching hospitals in Baghdad city. Adults of both gender who had history of hypertension for at least six months were included in the study. A questionnaire was developed to assess the knowledge, attitude and practice of those patients. More than 60% had good knowledge, 80% expressed good attitude while 24% recorded good practice. Analyses of data revealed that the score of knowledge is significantly associated with age (p=0.002) and gender (p=0.002). It was also directly related to the education level. (p=0.0001), duration of hypertension (p=0.041) and the presence of positive family history of the disease (p=0.0001). The attitude was significantly associated with age (p=0.046), level of education (p=0.008) and family history (p=0.006). The score of practice was significantly associated with age (p=.0008), and duration of hypertension (p=0.004). Hypertensive patients in our community have relatively good knowledge and attitude, but poor practice and compliance to treatment. Efforts are needed to increase the awareness through continuous health education in the health facilities and health promotional programs via the mass media. South East Asia Journal of Public Health Vol.7(1) 2017: 29-34